2019
DOI: 10.1002/icd.2130
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal complications are associated with social anxiety: Indirect effects through temperament

Abstract: The current investigation examines the relation between perinatal complications and social anxiety incorporating the potential indirect effect of child temperament. Participants were 149 children aged 9 to 12 years (Mage = 9.97, SDage = 1.00) screened for behavioural inhibition (BI) and assessed for social anxiety symptoms using parent and child reports. Participating families also reported on the presence of perinatal complications. Results indicated that children who experienced perinatal complications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Future interventions to improve social interaction skills should start before school entry to prevent long-term problems [95] and should emphasize the role of parents in promoting the social development of their children, especially for those born very and moderately preterm. Additionally, future studies that explore social inhibition as a developmental pathway to preterm individuals’ later psychopathology [96] and social problems [97] constitute an important direction to shed light on the mechanisms explaining preterm individuals’ long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Future interventions to improve social interaction skills should start before school entry to prevent long-term problems [95] and should emphasize the role of parents in promoting the social development of their children, especially for those born very and moderately preterm. Additionally, future studies that explore social inhibition as a developmental pathway to preterm individuals’ later psychopathology [96] and social problems [97] constitute an important direction to shed light on the mechanisms explaining preterm individuals’ long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Effect sizes for significant between-group differences were calculated as the difference between Fisher's Z scores (q = Z 1 − Z 2 ). Results employing an extreme group design using a cut point of 119 on the total BIQ to denote BI (n = 13) and non-BI (n = 81), as used in previous studies (Suarez, Morales, Metcalf, & Pérez-Edgar, 2019), can be found in our Supplementary Materials.…”
Section: Data Analysesmentioning
confidence: 99%
“…Just because there is a high heritability does not mean that environmental factors are not important. Suarez et al (2018) found that perinatal complications are related to social inhibition, which likely has a Prevalence and Heritability of AVPD relationship with AVPD. In addition, it is possible that some of the heritability of AVPD is due to behaviors learned in the family environment.…”
Section: Discussionmentioning
confidence: 99%